2018
DOI: 10.1021/acs.jpcc.7b12533
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Multilayer Cu Islands Embedded beneath the Surface of Graphite: Characterization and Fundamental Insights

Abstract: We present an extensive experimental study of the conditions under which Cu forms encapsulated islands under the top surface layers of graphite, as a result of physical vapor deposition of Cu on argon-ionbombarded graphite. When the substrate is held at 800 K during deposition, conditions are optimal for formation of encapsulated multilayer Cu islands. Deposition temperatures below 600 K favor adsorbed Cu clusters, while deposition temperatures above 800 K favor a different type of feature that is probably a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(97 citation statements)
references
References 68 publications
7
89
1
Order By: Relevance
“…Specifically, for Fe, h max =9 nm, whereas for Cu, h max =43 nm, so the Fe islands do not grow as tall. Second, for Cu, some islands have round tops rather than flat tops [10] whereas for Fe, only flat tops are observed. For Cu, the largest islands tend to have round tops, so these two differences may be related, e.g.…”
Section: Results From Experimentsmentioning
confidence: 97%
See 3 more Smart Citations
“…Specifically, for Fe, h max =9 nm, whereas for Cu, h max =43 nm, so the Fe islands do not grow as tall. Second, for Cu, some islands have round tops rather than flat tops [10] whereas for Fe, only flat tops are observed. For Cu, the largest islands tend to have round tops, so these two differences may be related, e.g.…”
Section: Results From Experimentsmentioning
confidence: 97%
“…Necessary conditions for Fe encapsulation include (i) activating the graphite surface with atomic-scale defects via Ar + ion bombardment, and (ii) depositing Fe on the activated graphite surface that is held at elevated temperature (T dep ). Our group has demonstrated that these conditions are effective for encapsulating a variety of metals, including Cu [10], Ru [11], and Dy [9]. Fe encapsulation is operational in a narrow T dep window of 875-900 K, with 900 K being the optimal temperature where the extent of encapsulation is high with minimal bare Fe on top of graphite [12].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One key goal of our analysis is to assess the relative stability of a single Cu atom adsorbed on the surface of 2H-MoS 2 (0001) versus intercalated underneath the surface. To this end, we calculate the Cu chemical potential defined as [30,31]…”
Section: Adsorption Diffusion and Intercalation Of A Cu Atom Amentioning
confidence: 99%